1984
DOI: 10.1016/0005-2728(84)90065-3
|View full text |Cite
|
Sign up to set email alerts
|

Optical picosecond studies of bacteriorhodopsin containing a sterically fixed retinal

Abstract: The photochemical behaviour of an analogous bacteriorhodopsin (9,12-Ph-BR) which contains the sterically fixed 9,12-phenylretinal has been investigated with picosecond spectroscopy. The following results have been obtained. No ground-state intermediate photoproduct is found in agreement with the previous observation that 9,12-Ph-BR does not exhibit proton pumping under illumination. The excited singlet state has a lifetime of ¢s-10 + 2 ps. This lifetime agrees favourably with the value calculated from the radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

1986
1986
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 19 publications
2
19
0
1
Order By: Relevance
“…In contrast to what was believed earlier,2 I‐460 is found to be all‐trans. It was also found that the torsional flexibility in native bR is responsible for the short lifetime of I‐460,7 in agreement with earlier work 10…”
Section: Introductionsupporting
confidence: 91%
“…In contrast to what was believed earlier,2 I‐460 is found to be all‐trans. It was also found that the torsional flexibility in native bR is responsible for the short lifetime of I‐460,7 in agreement with earlier work 10…”
Section: Introductionsupporting
confidence: 91%
“…9. The apomembrane (bacterioopsin) obtained was either reconstituted with 9,12-phenylretinal [10] or with all-trans and 13-cis retinal purified by high-pressure liquid chromatography. Reconstitution of the chromoproteins was followed spectroscopically in an Aminco DW2 spectrophotometer [11] and fluorescence emission spectra ()~ excitation 280 nm) recorded in a Perkin Elmer MPF 3 spectrofluorimeter.…”
Section: Methodsmentioning
confidence: 99%
“…First, retinal was extracted from the purple membrane and by doing this a chromophore-free suspension of bacterioopsin prepared [10]. Exciting this sample with light at 527 nm at the same intensity as used above did not give an ultraviolet emission within the dynamic range of our experiment.…”
Section: The Fluorescence Spectramentioning
confidence: 97%
“…To test the current hypothesis that it is the all-trans~ 13-cis isomerization that triggers the proton pumping mechanism, Polland et a/. (1984) carried out picosecond absorption spectroscopy and fluorescence measurements with a sterically fixed "9, 12-phenyl-retinal" reconstituted with bacterioopsin.…”
Section: Photoelectric Activity Of Dark-adapted Bacteriorhodopsinmentioning
confidence: 99%